2021
DOI: 10.22454/fammed.2021.866524
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Authorship of Family Medicine Publications, 2002-2017

Abstract: Background and Objectives: Representation of women in medicine is increasing, including in academic family medicine. Despite this, women continue to hold a minority of senior faculty and leadership roles. This study examines the trends of women first and senior authorship between 2002 and 2017 in five family medicine journals: Family Medicine, Journal of Family Practice, Journal of the American Board of Family Medicine, Annals of Family Medicine, and American Family Physician. The study also examines gender co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Among journals from those fields, women make up 16 to 17% of emergency medicine journal editorial board members and 35% of family medicine journal editorial boards. [24][25][26] Although determination of gender parity targets may not be straightforward, other journals have demonstrated that concerted efforts can improve gender balance. The Lancet journals committed to gender parity in 2018 following an internal review that showed an approximate 30% female representation on the editorial boards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among journals from those fields, women make up 16 to 17% of emergency medicine journal editorial board members and 35% of family medicine journal editorial boards. [24][25][26] Although determination of gender parity targets may not be straightforward, other journals have demonstrated that concerted efforts can improve gender balance. The Lancet journals committed to gender parity in 2018 following an internal review that showed an approximate 30% female representation on the editorial boards.…”
Section: Discussionmentioning
confidence: 99%
“…Among journals from those fields, women make up 16 to 17% of emergency medicine journal editorial board members and 35% of family medicine journal editorial boards. 24 -26…”
Section: Discussionmentioning
confidence: 99%
“…4 Women publish less as first authors and are less likely to have research mentors. 5,6 Women physicians are also evaluated differently than their men physician peers. 7 These gendered expectations contribute to women physicians' experiences of burnout.…”
Section: What Do We Know About the Practices Of Women Physicians?mentioning
confidence: 99%